Diversified cropping systems for inclusive and resilient agri-food system in Embu County - Mureithi, Catherine; Nyokabi, Miriam; Micheni, Alfred N.; Waswa, Boaz Shaban; Nchanji, Eileen Bogweh (2023)
The impacts of climate change in Eastern and Southern Africa (ESA), are already well known to farmers. Over 2 million people in Kenya face threat of food insecurity due to climate change. Maize production is particularly vulnerable to climate change. It is projected to face not only 15% climate-related declines in yield without adaptation but also challenges from diminished cropland suitability and poor agronomic inputs and management; degraded environmental bases with declining soil fertility and degraded water systems are already apparent. Given that maize-mixed systems cover over 75% of the cropping land in many places, it is critical to build climate resilience and de-risk through diversification.